ANALISIS KINERJA BADAN KETAHANAN PANGAN KABUPATEN DONGGALA - Lembah, Andi Rita (Katalogis, 2015)
This study aims to determine the performance of the Food Security How Donggala. This study used a qualitative approach to the informant as much as five (5) persons within the Food Security Agency Donggala. Data collected by using observation, meaning that the researchers directly observed according to a predetermined location research. Location research done purposively. The collected data were analyzed in stages based on the data information from the informant obtained through observation, interviews and documentation. The results showed that all five aspects used in measuring the performance of the Food Security Donggala in the public service, namely productivity, quality of service, responsiveness, responsibility, and accountability, There are three aspects that have not been going well, namely Productivity Aspect, Aspect and Aspect Quality of Service Accountability. Yet all three of these aspects very significant effect on the performance of the Food Security District. In the aspect of productivity is still a lot of programs and services that are not run effectively and efficiently in the implementation of the basic tasks and functions of the Food Security Donggala. For the aspects of quality of service, level of education and experience factors Food Security Agency employee Donggala still low so that affects the run basic tasks and functions. While the aspect of accountability is not going well, this is due to lack of understanding of employees who do not obey the rules set by the head.